TRAINING OF MICROSOFT MATHEMATICS TO IMPROVE THE QUALITY OF LEARNING METHODS FOR TEACHERS IN JUNIOR SECONDARY SCHOOLS (SMP AND MTs) AT PONOROGO EAST JAVA INDONESIA - Kwardiniya Andawaningtyas; Wuryansari Muharini Kusumawinahyu; Ani Budi Astuti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
All this time, mathematics has become the scourge for elementary and junior high school students, so that students are not well motivated to learn the material of Mathematics. Along with the development of computer technology, it can be used as one tool that can help the learning process. Mathematics software can be used to explain the difficult concepts in mathematics becomes easily, clearer, more interesting and fun. In Ponorogo, mathematics teachers have a meeting forum called the Subject Teacher Council (MGMP) of Mathematics. The general problems of the council is the less equality in opportunities of MGMP Mathematics teachers in Junior Secondary Schools (SMP and MTs) at Ponorogo to attain trainings for improving students skills in understanding the material of Mathematics and the limited insight of mathematics teachers about mathematics software that can be used as an instructional media of mathematics material. Therefore, the activity of microsoft mathematics training for mathematics teachers in Junior Secondary Schools at Ponorogo has been necessarily and urgently needed to improve the quality of learning methods. These software is open source software with less space requirement in the computer and easy installation.